2020
DOI: 10.3390/foods9060832
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Buckwheat Groats Processing on the Content and Bioaccessibility of Selected Minerals

Abstract: Adequate supply of minerals in the diet is necessary for the proper functioning of the human body. In recent years gluten-free diet, which rigorous forms may lead to deficiencies of mineral components (especially Mg, Mn, Zn and Cu), is becoming more and more popular. Buckwheat grains do not contain gluten, and their nutritional value is very high. They are often consumed in the form of groats, which are obtained from roasted and dehulled seeds. The purpose of the work was to determine how conducting the buckwh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…The average Zn content in wheat grains worldwide is 28.5 mg/kg, which is slightly higher than in our case [ 42 ]. Klepacka et al [ 10 ] found differences between hulled and dehulled common buckwheat grains in terms of Mg, Mn, Zn and Cu content. Dehulled grains contained higher concentration of Mg and Zn, while Mn content had decreased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average Zn content in wheat grains worldwide is 28.5 mg/kg, which is slightly higher than in our case [ 42 ]. Klepacka et al [ 10 ] found differences between hulled and dehulled common buckwheat grains in terms of Mg, Mn, Zn and Cu content. Dehulled grains contained higher concentration of Mg and Zn, while Mn content had decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of such whole grain foods are wheat groats, spelt rice, spelt groats, spelt kasha, barley groats, barley kasha, pot barley, barley porridge, barley pearls, whole oat groats, whole grain oats, steel cut oats, oat rice or a mixture of different grains (rice, spelt and barley, etc.) [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The micronutrients in buckwheat are higher than in cereal grains, and their concentration is mainly confined to the seed coat, hull, and aleurone layers (Orožen et al, 2012 ). The minerals like zinc, copper, and potassium become readily available for absorption after enzymatic digestion into a soluble form (Klepacka et al, 2020 ). The diet available for gluten‐free consumers is low in vitamins and minerals, and the incorporation of buckwheat in gluten‐free diets increases the concentration of vitamins and essential minerals in their diet (Mir et al, 2014 ).…”
Section: Nutritional Constituents Of Buckwheatmentioning
confidence: 99%
“…Гречневая крупа является одним из любимых продуктов не только россиян, но и за рубежом [1][2][3]. Алтайский край традиционно и заслуженно является лидером в России по выработке гречневой крупы [4].…”
Section: Introductionunclassified